Improving Students' Public Speaking Skills Using the Drill Method - Sausan Salsabila; Purwanto Purwanto; Laili Syarifah (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Public speaking or public speaking skills are one of the most essential language skills to master, including for junior high school level students. This is because speaking skills are beneficial for expressing oneself, such as conveying thoughts and ideas according to the goals you want to achieve. However, many students still need good public speaking, including students at Mts Walisongo 2. Community service activities are carried out at Mts Walisongo 2 in Sukomakmur Village, Kajoran District, using the Asset Based Community Development (ABCD) approach. The service team used the drill learning method to improve students' public speaking skills in carrying out the activities. This mentoring was implemented successfully and significantly impacted the public speaking skills of Mts Walisongo 2 students.